Modified composite catalyst, preparation method thereof and application of modified composite catalyst in methyl methacrylate synthesis reaction
By developing modified composite catalysts and utilizing the characteristics of microporous-mesoporous composite materials, the problems of low methacrylic acid conversion rate and low yield in the production of methyl methacrylate were solved, achieving higher conversion rate and Selectivity.
Patent Information
- Application Number
- CN202310875898.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-17
Smart Images

Figure CN119327506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fine chemicals, and in particular to a modified composite catalyst and a preparation method thereof, as well as application of the modified composite catalyst in a methyl methacrylate synthesis reaction. Background Art
[0002] As an important type of organic chemical product and organic chemical raw material, the industrial production level and production capacity of methyl methacrylate (MMA) have an important impact on the development of my country's chemical industry. MMA is mainly used in industries such as organic glass (PMMA), coatings, textiles, adhesives, leather, papermaking, floor polishing, unsaturated resin modification, methacrylate esters, wood impregnation agents, printing and dyeing auxiliaries, and plasticizers for plastics. In recent years, the demand for MMA polymers, profiles, plates, coatings, emulsions, etc. has increased at home and abroad, and the application fields are constantly expanding, which has promoted the rapid development of the MMA industry.
[0003] Esterification catalyst is the core technology of MMA production. For the esterification reaction of methacrylic acid and methanol, the traditional production process using inorganic acids such as sulfuric acid, phosphoric acid, and boric acid as catalysts has been gradually eliminated. Using organic acids such as p-toluenesulfonic acid as catalysts also has the disadvantages of serious environmental pollution, low selectivity, and difficult product separation. In comparison, esterification catalysts for multiphase reactions are currently an active research field. In the latest reports, researchers have continuously tried to use acidic resins, organotin compounds, rare earth solid superacids, Lewis acids and other catalysts in the synthesis of carboxylic esters, and have achieved meaningful experimental results.
[0004] At present, acidic cation exchange resins are widely used in industry to produce methyl methacrylate. Cation exchange resins show advantages such as good stability, high selectivity, low cost, and easy separation in esterification reactions. However, the cation exchange resin itself has poor heat resistance (generally it will decompose at temperatures not higher than 250°C), small specific surface area and pore volume, and easy swelling of cation exchange resins. As esterification catalysts, the reaction activity is poor and the ester yield is low. With the increasing demand for MMA, the prospect of synthesizing methyl methacrylate using green and environmentally friendly processes is broad. At present, solid-supported esterification catalysts are receiving more and more attention in the synthesis of methyl methacrylate. For researchers, developing esterification catalysts with excellent performance, improving reaction efficiency, and inhibiting the formation of by-products are important future work directions. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low methacrylic acid conversion rate and low methyl methacrylate yield in the current methyl methacrylate production process, and to provide a modified composite catalyst and a preparation method thereof and application in a methyl methacrylate synthesis reaction. The modified composite catalyst is used in a methacrylic acid esterification reaction to obtain a higher methacrylic acid conversion rate and methyl methacrylate selectivity.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modified composite catalyst, wherein the pore size of the modified composite catalyst is bimodal distribution, the first pore size is 0.4-0.6nm, and the second pore size is 9-15nm; the modified composite catalyst is obtained by acidification treatment of a microporous-mesoporous composite material, wherein the microporous-mesoporous composite material includes a hydrogen-type ZSM-35 molecular sieve and alumina, and based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 30-90% by weight, and the content of the alumina is 10-70% by weight.
[0007] The second aspect of the present invention provides a method for preparing the aforementioned modified composite catalyst, wherein the preparation method comprises:
[0008] (1) mixing the microporous-mesoporous composite material with an acid aqueous solution for contact reaction to obtain a mixture;
[0009] (2) filtering the mixture to obtain a solid product, washing, drying and calcining the solid product to obtain a modified composite catalyst.
[0010] The third aspect of the present invention provides an application of the modified composite catalyst described above in the synthesis reaction of methyl methacrylate.
[0011] Through the above technical solution, compared with the prior art, the technical solution of the present invention has the following advantages:
[0012] (1) The modified composite catalyst provided by the present invention has a stable structure, does not deform or swell during the reaction, and has a high methacrylic acid conversion rate and high methyl methacrylate selectivity when used to synthesize methyl methacrylate.
[0013] (2) The raw materials of the modified composite catalyst provided by the present invention are easily available, the preparation method is simple, the conditions are easy to control, and the product has good reproducibility.
[0014] (3) When the modified composite catalyst provided by the present invention is used to synthesize methyl methacrylate, the process conditions are mild and the requirements for the reaction device are not high.
[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0017] Figure 1 is the XRD spectrum of the modified composite catalyst A prepared in Example 1 of the present invention;
[0018] Figure 2 This is the pore size distribution diagram of the modified composite catalyst A prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] As mentioned above, the first aspect of the present invention provides a modified composite catalyst, characterized in that the pore size of the modified composite catalyst is bimodal, the first pore size is 0.4-0.6nm, and the second pore size is 9-15nm; the modified composite catalyst is obtained by acidification treatment of a microporous-mesoporous composite material, wherein the microporous-mesoporous composite material includes a hydrogen-type ZSM-35 molecular sieve and alumina, and based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 30-90% by weight, and the content of the alumina is 10-70% by weight.
[0021] According to the present invention, preferably, the pore size of the modified composite catalyst is bimodal, with a first pore size of 0.5-0.6 nm and a second pore size of 9.8-14.8 nm.
[0022] The inventors of the present invention have found that in the prior art, the esterification catalysts used to produce methyl methacrylate are divided into two categories: homogeneous and heterogeneous. Among them, homogeneous catalysts mainly include inorganic acid solutions and organic acids, and heterogeneous catalysts mainly include solid acids and cation exchange resins. The advantages of homogeneous catalysts are low price and good catalytic activity, but they are gradually eliminated due to defects such as difficulty in separating products from catalysts, more side reactions, and easy corrosion of equipment. Although solid acid esterification catalysts solve the problems of difficult product separation and serious equipment corrosion, they are rarely used in industrial production due to disadvantages such as poor catalytic activity, high reaction temperature, and low product selectivity. Compared with the above catalysts, the production of methyl methacrylate using acidic cation exchange resins as esterification catalysts is the main process for industrial applications. Resin catalysts have the advantages of high selectivity, low cost and easy separation, but the yield of methyl methacrylate is low during the esterification reaction of methyl methacrylate, and the high temperature resistance is also poor. Resin is an organic polymer material, which is easy to swell in organic solvents, easy to deform or even decompose in high temperature environments, which is the main reason for the poor temperature resistance of resin catalysts. Developing a new solid catalyst system to make up for the performance defects of resin catalysts is a good way to solve the problem. If you want to solve the structural defects of the resin catalyst itself and improve the catalytic performance of the esterification catalyst, you must first choose a new material with excellent structural characteristics. Compared with the resin catalyst, the hydrogen-type ZSM-35 molecular sieve has a certain pore structure and surface acidity, which is suitable for catalyzing the esterification reaction of small molecules. However, the pore size of the ZSM-35 molecular sieve is small (average pore size 0.4-0.6nm), which may inhibit the diffusion of macromolecular products during the reaction; and the number of acid sites on the surface of the ZSM-35 molecular sieve is small, and the efficiency of catalytic esterification reaction is low. Therefore, the ZSM-35 molecular sieve material is not suitable for directly catalyzing the synthesis reaction of methyl methacrylate as a catalyst. If the ZSM-35 molecular sieve is compounded with a material with a mesoporous structure, the pore distribution can be improved, which is conducive to the diffusion of macromolecular reactants and products. The pores of the alumina material itself belong to the mesoporous category, and the precursor of the alumina material has good adhesion. If alumina is used as the mesoporous material and compounded with the ZSM-35 molecular sieve, it can not only solve the pore distribution problem, but also solve the molding problem of the ZSM-35 molecular sieve.
[0023] The inventors of the present invention have also found that the surface acidity of the microporous-mesoporous composite material obtained by compounding aluminum oxide with ZSM-35 molecular sieve is still relatively weak, and the efficiency of catalytic esterification reaction is relatively poor. If the surface of the microporous-mesoporous composite material is modified with sulfuric acid in an appropriate manner to increase the acid density and acid strength, an esterification catalyst with good catalytic performance will be obtained. When the catalyst is used for the esterification reaction of methacrylic acid and methanol, it can show good catalytic activity and methyl methacrylate selectivity.
[0024] According to the present invention, the specific surface area of the modified composite catalyst is 220-380m 2 / g, pore volume is 0.2-0.8cm 3 / g; preferably, the specific surface area of the modified composite catalyst is 250-350m 2 / g, pore volume is 0.3-0.7cm 3 / g; More preferably, the specific surface area of the modified composite catalyst is 287-331m 2 / g, pore volume is 0.4-0.6cm 3 In the present invention, the modified composite catalyst having the above-mentioned specific parameters is used, so that the catalyst has better catalytic activity and ester selectivity when used in methacrylic acid esterification reaction.
[0025] According to the present invention, the specific surface area of the microporous-mesoporous composite material is 250-400m 2 / g, pore volume is 0.3-0.9cm 3 / g; Preferably, the specific surface area of the microporous-mesoporous composite material is 280-370m 2 / g, pore volume is 0.4-0.8cm 3 / g; More preferably, the specific surface area of the microporous-mesoporous composite material is 304-344m 2 / g, pore volume is 0.5-0.7cm 3 In the present invention, the microporous-mesoporous composite material having the above-mentioned specific parameters is used, so that the further prepared modified composite catalyst has better catalytic activity and ester selectivity when used in methacrylic acid esterification reaction.
[0026] According to the present invention, based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 40-80% by weight, and the content of the aluminum oxide is 20-60% by weight; more preferably, based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 50-70% by weight, and the content of the aluminum oxide is 30-50% by weight. In the present invention, the use of the aforementioned specific content of hydrogen-type ZSM-35 molecular sieve and aluminum oxide can make the prepared microporous-mesoporous composite material have better catalytic activity and ester selectivity when used in methacrylic acid esterification reaction.
[0027] According to the present invention, the preparation method of the microporous-mesoporous composite material comprises: uniformly mixing hydrogenated ZSM-35 molecular sieve, aluminum-containing precursor and extrusion aid, adding dilute nitric acid, stirring evenly and extruding, and obtaining the microporous-mesoporous composite material after drying and calcining.
[0028] According to the present invention, the SiO2 / Al2O3 molar ratio of the hydrogen-type ZSM-35 molecular sieve is 10-200; preferably, the SiO2 / Al2O3 molar ratio of the ZSM-35 zeolite molecular sieve is 20-90. In the present invention, the ZSM-35 molecular sieve can be obtained by commercial means. Specifically, the ZSM-35 molecular sieve is more preferably: a ZSM-35 molecular sieve with a SiO2 / Al2O3 molar ratio of 20 is purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; a ZSM-35 molecular sieve with a SiO2 / Al2O3 molar ratio of 30 is purchased from Tianjin Nanhua Catalyst Co., Ltd.; a ZSM-35 molecular sieve with a SiO2 / Al2O3 molar ratio of 90 is purchased from Nanjing Jicang Nanotechnology Co., Ltd.
[0029] According to the present invention, the aluminum-containing precursor is selected from one or more of pseudo-boehmite, aluminum sol, monohydrate soft stone and aluminum hydroxide gel, preferably pseudo-boehmite. The oxide remaining after the aluminum-containing precursor is calcined is aluminum oxide. In the present invention, the pseudo-boehmite can be obtained by commercial purchase or preparation. In the present invention, specifically, the pseudo-boehmite includes: German imported pseudo-boehmite powder with model SB (purchased from Beijing Asia Pacific Aohua Chemical Additives Co., Ltd., with a specific surface area of 241m 2 / g, pore volume 0.53cm 3 / g), pseudo-boehmite powder of model P-DF-09-LSi (purchased from Shandong Aluminum Co., Ltd., with a specific surface area of 286m 2 / g, pore volume 1.08cm 3 / g) and macroporous pseudo-boehmite powder of model PB-0101 (purchased from Zibo Hengqi Powder New Material Co., Ltd., with a specific surface area of 327m 2 / g, pore volume 1.02cm 3 / g) in one or more.
[0030] According to the present invention, the extrusion aid is one or more of sesbania powder, cellulose, polyethylene glycol, polyvinyl alcohol or starch, preferably sesbania powder and polyethylene glycol.
[0031] According to the present invention, the mass percentage concentration of the dilute nitric acid is 0.5-15%, preferably 1-10%.
[0032] According to the present invention, the weight ratio of the hydrogenated ZSM-35 molecular sieve, the aluminum-containing precursor and the extrusion aid is 1:(0.1-3.5):(0.03-0.40), preferably 1:(0.3-2.5):(0.05-0.30).
[0033] According to the present invention, the drying conditions are preferably: drying temperature 70-160° C., and drying time 4-10 hours.
[0034] According to the present invention, the calcination conditions are preferably: the calcination temperature may be 450-650° C., preferably 500-600° C.; the calcination time may be 3-20 hours, preferably 5-16 hours.
[0035] According to the present invention, the microporous-mesoporous composite material may be in the shape of a sphere, a granule, a strip, a cylinder, a toothed ball or a clover leaf.
[0036] The second aspect of the present invention provides a method for preparing the aforementioned modified composite catalyst, wherein the preparation method comprises:
[0037] (1) contacting the microporous-mesoporous composite material with an aqueous acid solution to react and obtain a mixture;
[0038] (2) The mixture is filtered, washed, dried and calcined to obtain a modified composite catalyst.
[0039] According to the present invention, the acid is sulfuric acid.
[0040] According to the present invention, the molar concentration of the aqueous solution of the acid is 0.05-0.3 mol / L, preferably 0.1-0.2 mol / L.
[0041] According to the present invention, the weight ratio of the microporous-mesoporous composite material to the acid aqueous solution is 1:(3-50), preferably 1:(5-30).
[0042] According to the present invention, the conditions for contacting the microporous-mesoporous composite material with the acid aqueous solution for reaction include: the temperature can be 40-90°C, preferably 50-80°C; the time can be 0.2-8h, preferably 0.5-5h. Preferably, in order to achieve a better mixing effect, the microporous-mesoporous composite material can be rapidly stirred or ultrasonically improved during the contact reaction with the acid aqueous solution to improve the reaction efficiency.
[0043] According to the present invention, the mixture is filtered to obtain a solid product, wherein the filtration has no special requirements and can be a filtration method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtration process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.
[0044] According to the present invention, the solid product is washed, dried and calcined, wherein the method for washing the solid product has no special requirements, for example, the solid product can be washed with deionized water, the volume ratio of deionized water to the solid product can be 5-20, and the number of washing times can be 2-8 times.
[0045] According to the present invention, the drying conditions include: the temperature can be 70-130° C., preferably 90-120° C.; the time can be 1-30 hours, preferably 3-20 hours.
[0046] According to the present invention, the calcination conditions include: the temperature can be 300-500° C., preferably 350-450° C.; the time can be 3-15 hours, preferably 5-10 hours.
[0047] The third aspect of the present invention provides an application of the modified composite catalyst described above in the synthesis reaction of methyl methacrylate.
[0048] According to the present invention, the application comprises: contacting methacrylic acid and methanol with the modified composite catalyst simultaneously.
[0049] According to the present invention, the contact conditions of methacrylic acid and methanol with the catalyst include: the contact temperature can be 40-150°C, preferably 60-120°C; the contact pressure can be 0.01-5.0MPa, preferably 0.1-3.0Mpa; the mass space velocity of methacrylic acid can be 0.01-30h -1 , preferably 0.1-10h -1 ; The mass space velocity of methanol can be 0.01-50h -1 , preferably 0.1-30h -1 .
[0050] The present invention will be described in detail below through examples.
[0051] In the following examples and comparative examples:
[0052] The XRD test of the sample was carried out on an X'Pert MPD X-ray powder diffractometer of Philips Company of the Netherlands, with a Cu Kα target and a scanning range of 2θ=5-90°.
[0053] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 40°C for 4 hours before measurement, and the specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0054] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.
[0055] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0056] The muffle furnace is produced by CARBOLITE, model CWF1100.
[0057] Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.
[0058] Example 1
[0059] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0060] (1) Preparation of microporous-mesoporous composite materials
[0061] 60 g of ZSM-35 molecular sieve (SiO2 / Al2O3=30) was mixed evenly with 57 g of pseudo-boehmite powder of model P-DF-09-LSi and 6 g of sesbania powder, and 90 g of 3% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a cylindrical shape with a diameter of 2 mm and a length of 2 mm; dried at 110°C for 6 hours, and finally calcined at 580°C for 8 hours to obtain a microporous-mesoporous composite material A.
[0062] Based on the total weight of the microporous-mesoporous composite material A, the content of ZSM-35 molecular sieve is 60% by weight and the content of alumina is 40% by weight. The specific surface area of the microporous-mesoporous composite material A is 344 m 2 / g, and the pore volume is 0.7ml / g.
[0063] (2) Preparation of modified composite catalyst
[0064] In a round-bottom flask, 10g of microporous-mesoporous composite material A was mixed with 100g of 0.15mol / L sulfuric acid solution, heated to 70°C, and stirred under reflux for 2 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 6 times with 100ml of deionized water, dried in air at 110°C for 8 hours, and then calcined at 400°C for 7h to obtain a modified composite catalyst A.
[0065] Figure 1It is the XRD spectrum of the modified composite catalyst A. It can be seen that the wide-angle x-ray diffraction angles of the sample are mainly: 2θ=9.4°, 22.4°, 22.7°, 23.3°, 23.7°, 24.5°, 25.3°, 36.8°, 42.8° and 66.9°. Among them, the diffraction signals of 2θ=9.4°, 22.4°, 22.7°, 23.3°, 23.7°, 24.5° and 25.3° are consistent with the diffraction spectrum of ZSM-35 molecular sieve, indicating that the crystal phase of ZSM-35 molecular sieve has not changed significantly during the catalyst preparation process, and still maintains a good FER type topological framework structure. The diffraction signals at 2θ=36.8°, 42.8° and 66.9° are consistent with the γ-Al2O3 diffraction spectrum, indicating that after the modified composite catalyst A is calcined at 580°C, the pseudo-boehmite is dehydrated and mainly exists in the γ-Al2O3 crystal phase.
[0066] Figure 2 This is the pore size distribution diagram of the modified composite catalyst A. As can be seen from the figure, the sample has an obvious double-pore structure, and the double pore diameters are 0.5nm and 12.3nm respectively. Among them, the pore with a pore size of 0.5nm is provided by the hydrogen-type ZSM-35 molecular sieve, and the mesoporous pore with a most probable pore size of 12.3nm is provided by alumina.
[0067] The specific surface area of modified composite catalyst A is 331m 2 / g, and the pore volume is 0.6ml / g.
[0068] (3) Catalyst reaction performance evaluation
[0069] The esterification performance of the catalyst was evaluated in a fixed bed reactor. 5.0 g of the modified composite catalyst A was loaded into a stainless steel fixed bed reactor with an inner diameter of 8 mm, the reaction temperature was 95°C, the reaction pressure was 0.5 MPa, and the weight space velocity of methacrylic acid was 1.0 h -1 , the weight space velocity of methanol is 2.7h -1 The reaction time was 20 hours. After cooling, the product was analyzed by an Agilent 7890A gas chromatograph equipped with a FFAP capillary column and a hydrogen flame detector (FID), using programmed temperature and correction factors for quantitative analysis. The methacrylic acid conversion rate was 97.0%, and the selectivity of methyl methacrylate was 99.7%.
[0070] Example 2
[0071] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0072] (1) Preparation of microporous-mesoporous composite materials
[0073] 70 g of ZSM-35 molecular sieve (SiO2 / Al2O3=90) was mixed evenly with 41 g of SB pseudo-boehmite powder and 4 g of polyethylene glycol, and then 75 g of 5% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a toothed ball shape with a diameter of 3 mm; dried at 130°C for 4 hours, and finally calcined at 550°C for 12 hours to obtain a microporous-mesoporous composite material B.
[0074] Based on the total weight of the microporous-mesoporous composite material B, the content of ZSM-35 molecular sieve is 70% by weight and the content of alumina is 30% by weight. The specific surface area of the microporous-mesoporous composite material B is 335 m 2 / g, and the pore volume is 0.5ml / g.
[0075] (2) Preparation of modified composite catalyst
[0076] In a round-bottom flask, 10g of microporous-mesoporous composite material B was mixed with 300g of 0.1mol / L sulfuric acid solution, heated to 80°C, and stirred under reflux for 0.5 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 4 times with 200ml of deionized water, dried in air at 120°C for 3 hours, and then calcined at 350°C for 10 hours to obtain a modified composite catalyst B.
[0077] The modified composite catalyst B has an obvious double-channel structure, and the double-pore diameters are 0.6nm and 11.7nm respectively.
[0078] The specific surface area of the modified composite catalyst B is 302m 2 / g, and the pore volume is 0.4ml / g.
[0079] (3) Catalyst reaction performance evaluation
[0080] The esterification performance of catalyst B was tested according to the method of step (3) in Example 1. The methacrylic acid conversion rate was 96.8%, and the selectivity of methyl methacrylate was 99.5%.
[0081] Example 3
[0082] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0083] (1) Preparation of microporous-mesoporous composite materials
[0084] 50g ZSM-35 molecular sieve (SiO2 / Al2O3=20) was mixed evenly with 71g PB-0101 pseudo-boehmite powder and 12g sesbania powder, and 85g 8% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a spherical shape with a diameter of 2mm; dried at 90°C for 10 hours, and finally calcined at 600°C for 5 hours to obtain a microporous-mesoporous composite material C.
[0085] Based on the total weight of the microporous-mesoporous composite material C, the content of ZSM-35 molecular sieve is 50% by weight and the content of alumina is 50% by weight. The specific surface area of the microporous-mesoporous composite material C is 304 m2 / g, and the pore volume is 0.6 ml / g.
[0086] (2) Preparation of modified composite catalyst
[0087] In a round-bottom flask, 10 g of microporous-mesoporous composite material C was mixed with 50 g of 0.2 mol / L sulfuric acid solution, heated to 50 ° C, and refluxed for 5 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 8 times with 100 ml of deionized water, dried in air at 90 ° C for 20 hours, and then calcined at 450 ° C for 5 hours to obtain a modified composite catalyst C.
[0088] The modified composite catalyst C has an obvious double-channel structure, and the double-pore diameters are 0.5nm and 13.9nm respectively.
[0089] The specific surface area of the modified composite catalyst C is 287m 2 / g, and the pore volume is 0.5ml / g.
[0090] (3) Catalyst reaction performance evaluation
[0091] The esterification performance of catalyst C was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 96.5%, and the selectivity of methyl methacrylate was 99.4%.
[0092] Example 4
[0093] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0094] (1) Preparation of microporous-mesoporous composite materials
[0095] 80 g of ZSM-35 molecular sieve (SiO2 / Al2O3=90) was mixed evenly with 27 g of SB pseudo-boehmite powder and 8 g of sesbania powder, and then 80 g of 2% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a toothed ball shape with a diameter of 3 mm; dried at 130°C for 4 hours, and finally calcined at 550°C for 12 hours to obtain a microporous-mesoporous composite material D.
[0096] Based on the total weight of the microporous-mesoporous composite material D, the content of ZSM-35 molecular sieve is 80% by weight and the content of alumina is 20% by weight. The specific surface area of the microporous-mesoporous composite material D is 370 m 2 / g, and the pore volume is 0.4ml / g.
[0097] (2) Preparation of modified composite catalyst
[0098] In a round-bottom flask, 10g of microporous-mesoporous composite material D was mixed with 300g of 0.08mol / L sulfuric acid solution, heated to 80°C, and stirred under reflux for 0.5 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 4 times with 200ml of deionized water, dried in air at 120°C for 3 hours, and then calcined at 350°C for 10 hours to obtain a modified composite catalyst D.
[0099] The modified composite catalyst D has an obvious double-channel structure, and the double-pore diameters are 0.6nm and 10.9nm respectively.
[0100] The specific surface area of modified composite catalyst D is 350 m 2 / g, and the pore volume is 0.3ml / g.
[0101] (3) Catalyst reaction performance evaluation
[0102] The esterification performance of catalyst D was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 95.8%, and the selectivity of methyl methacrylate was 99.0%.
[0103] Example 5
[0104] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0105] (1) Preparation of microporous-mesoporous composite materials
[0106] 40 g of ZSM-35 molecular sieve (SiO2 / Al2O3=20) was mixed evenly with 86 g of pseudo-boehmite powder of model P-DF-09-LSi and 10 g of sesbania powder, and then 95 g of 10% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a spherical shape with a diameter of 2 mm; dried at 90°C for 10 hours, and finally calcined at 600°C for 5 hours to obtain a microporous-mesoporous composite material E.
[0107] Based on the total weight of the microporous-mesoporous composite material E, the content of ZSM-35 molecular sieve is 40% by weight and the content of alumina is 60% by weight. The specific surface area of the microporous-mesoporous composite material E is 280 m 2 / g, and the pore volume is 0.8ml / g.
[0108] (2) Preparation of modified composite catalyst
[0109] In a round-bottom flask, 10 g of microporous-mesoporous composite material E was mixed with 50 g of 0.25 mol / L sulfuric acid solution, heated to 50 ° C, and refluxed for 5 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 8 times with 100 ml of deionized water, dried in air at 90 ° C for 20 hours, and then calcined at 450 ° C for 5 hours to obtain a modified composite catalyst E.
[0110] The modified composite catalyst E has an obvious double-channel structure, and the double-pore diameters are 0.5nm and 14.2nm respectively.
[0111] The specific surface area of the modified composite catalyst E is 250 m 2 / g, and the pore volume is 0.7ml / g.
[0112] (3) Catalyst reaction performance evaluation
[0113] The esterification performance of catalyst E was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 95.5%, and the selectivity of methyl methacrylate was 98.7%.
[0114] Example 6
[0115] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0116] (1) Preparation of microporous-mesoporous composite materials
[0117] 90 g of ZSM-35 molecular sieve (SiO2 / Al2O3=90) was mixed evenly with 14 g of SB pseudo-boehmite powder and 8 g of sesbania powder, and 70 g of 15% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a toothed ball shape with a diameter of 3 mm; dried at 160°C for 4 hours, and finally calcined at 480°C for 20 hours to obtain a microporous-mesoporous composite material F.
[0118] Based on the total weight of the microporous-mesoporous composite material F, the content of ZSM-35 molecular sieve is 90% by weight and the content of alumina is 10% by weight. The specific surface area of the microporous-mesoporous composite material F is 400 m 2 / g, and the pore volume is 0.3ml / g.
[0119] (2) Preparation of modified composite catalyst
[0120] In a round-bottom flask, 10g of microporous-mesoporous composite material F was mixed with 300g of 0.05mol / L sulfuric acid solution, heated to 90°C, and refluxed and stirred for 0.2 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed twice with 150ml of deionized water, dried in air at 130°C for 1 hour, and then calcined at 300°C for 15h to obtain a modified composite catalyst F.
[0121] The modified composite catalyst F has an obvious double-channel structure, and the double-pore diameters are 0.6nm and 9.8nm respectively.
[0122] The specific surface area of the modified composite catalyst F is 380 m 2 / g, and the pore volume is 0.2ml / g.
[0123] (3) Catalyst reaction performance evaluation
[0124] The esterification performance of catalyst F was tested according to the method of step (3) in Example 1. The methacrylic acid conversion rate was 95.0%, and the selectivity of methyl methacrylate was 98.3%.
[0125] Example 7
[0126] This embodiment is intended to illustrate the modified composite catalyst prepared by the present invention.
[0127] (1) Preparation of microporous-mesoporous composite materials
[0128] 30 g of ZSM-35 molecular sieve (SiO2 / Al2O3=20) was mixed evenly with 100 g of pseudo-boehmite powder of model P-DF-09-LSi and 12 g of sesbania powder, and 105 g of 0.5% nitric acid was added. After stirring evenly, the mixture was extruded and cut into a spherical shape with a diameter of 2 mm; dried at 70°C for 10 hours, and finally calcined at 650°C for 3 hours to obtain a microporous-mesoporous composite material G.
[0129] Based on the total weight of the microporous-mesoporous composite material G, the content of ZSM-35 molecular sieve is 30% by weight and the content of alumina is 70% by weight. The specific surface area of the microporous-mesoporous composite material G is 250 m 2 / g, and the pore volume is 0.9ml / g.
[0130] (2) Preparation of modified composite catalyst
[0131] In a round-bottom flask, 10g of microporous-mesoporous composite material G was mixed with 50g of 0.3mol / L sulfuric acid solution, heated to 40°C, and refluxed for 8 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 6 times with 100ml of deionized water, dried in air at 70°C for 30 hours, and then calcined at 500°C for 3h to obtain a modified composite catalyst G.
[0132] The modified composite catalyst G has an obvious double-channel structure, and the double-pore diameters are 0.5nm and 14.8nm respectively.
[0133] The specific surface area of the modified composite catalyst G is 220 m 2 / g, and the pore volume is 0.8ml / g.
[0134] (3) Catalyst reaction performance evaluation
[0135] The esterification performance of catalyst G was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 94.7%, and the selectivity of methyl methacrylate was 98.0%.
[0136] Comparative Example 1
[0137] (1) Preparation of microporous-mesoporous composite materials
[0138] 95 g of ZSM-35 molecular sieve (SiO2 / Al2O3=90) was mixed evenly with 7 g of SB pseudo-boehmite powder and 3 g of sesbania powder, and 55 g of 20% nitric acid was added. After stirring evenly, the mixture was extruded and cut into cylindrical particles with a diameter of 2 mm and a height of 2 mm; dried at 160°C for 4 hours, and finally calcined at 430°C for 20 hours to obtain a microporous-mesoporous composite material D1.
[0139] Based on the total weight of the microporous-mesoporous composite material D1, the content of ZSM-35 molecular sieve is 95% by weight and the content of alumina is 5% by weight. The specific surface area of the microporous-mesoporous composite material D1 is 427 m 2 / g, and the pore volume is 0.26ml / g.
[0140] (2) Preparation of modified composite catalyst
[0141] In a round-bottom flask, 10g of microporous-mesoporous composite material D1 was mixed with 200g of 0.02mol / L sulfuric acid solution, heated to 90°C, and stirred under reflux for 0.2 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed twice with 150ml of deionized water, dried in air at 130°C for 1 hour, and then calcined at 280°C for 15h to obtain a modified composite catalyst D1.
[0142] The specific surface area of the modified composite catalyst D1 is 394m 2 / g, the pore volume is 0.18ml / g, and the double pore diameters are 0.6nm and 12.1nm respectively.
[0143] (3) Catalyst reaction performance evaluation
[0144] The esterification performance of catalyst D1 was tested according to the method of step (3) in Example 1. The methacrylic acid conversion rate was 85.5%, and the selectivity of methyl methacrylate was 95.2%.
[0145] Comparative Example 2
[0146] (1) Preparation of microporous-mesoporous composite materials
[0147] 12g ZSM-35 molecular sieve (SiO2 / Al2O3=20) was mixed evenly with 125g P-DF-09-LSi pseudo-boehmite powder and 15g polyethylene glycol, and then 110g 2% nitric acid was added. After stirring evenly, the mixture was extruded and cut into spherical shapes with a diameter of 2mm; dried at 70°C for 10 hours, and finally calcined at 700°C for 3 hours to obtain a microporous-mesoporous composite material D2.
[0148] Based on the total weight of the microporous-mesoporous composite material D2, the content of ZSM-35 molecular sieve is 12% by weight and the content of alumina is 88% by weight. The specific surface area of the microporous-mesoporous composite material D2 is 234 m 2 / g, and the pore volume is 0.94ml / g.
[0149] (2) Preparation of modified composite catalyst
[0150] In a round-bottom flask, 10g of microporous-mesoporous composite material D2 was mixed with 40g of 0.5mol / L sulfuric acid solution, heated to 30°C, and refluxed for 4 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 6 times with 100ml of deionized water, dried in air at 70°C for 30 hours, and then calcined at 550°C for 6h to obtain a modified composite catalyst D2.
[0151] The specific surface area of the modified composite catalyst D2 is 203m 2 / g, the pore volume is 0.85ml / g, and the double pore diameters are 0.5nm and 13.5nm respectively.
[0152] (3) Catalyst reaction performance evaluation
[0153] The esterification performance of catalyst D2 was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 83.4%, and the selectivity of methyl methacrylate was 94.8%.
[0154] Comparative Example 3
[0155] (1) Preparation of shaped zeolite molecular sieve materials
[0156] After 100g ZSM-35 molecular sieve (SiO2 / Al2O3=30) and 6g sesbania powder are mixed evenly, 85g 3% nitric acid is added, and after stirring evenly, it is extruded and cut into a cylindrical shape with a diameter of 2mm and a length of 2mm; dried at 110°C for 6 hours, and finally calcined at 580°C for 8 hours to obtain a shaped zeolite molecular sieve material.
[0157] (2) Preparation of modified catalyst
[0158] In a round-bottom flask, 10g of the formed zeolite molecular sieve material was mixed with 100g of a sulfuric acid solution with a concentration of 0.15mol / L, heated to 70°C, and refluxed and stirred for 2 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 6 times with 100ml of deionized water, dried in air at 110°C for 8 hours, and then calcined at 400°C for 7h to obtain a modified catalyst D3.
[0159] The specific surface area of modified catalyst D3 is 418m 2 / g, and the pore volume is 0.15ml / g.
[0160] (3) Catalyst reaction performance evaluation
[0161] The esterification performance of catalyst D3 was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 81.4%, and the selectivity of methyl methacrylate was 94.1%.
[0162] Comparative Example 4
[0163] (1) Preparation of shaped alumina
[0164] After mixing 143g of pseudo-boehmite powder of model P-DF-09-LSi and 8g of sesbania powder, add 100g of 3% dilute nitric acid, stir evenly, extrude and cut into a cylindrical shape with a diameter of 2mm and a length of 2mm; dry at 110°C for 6 hours, and finally calcine at 580°C for 8 hours to obtain shaped alumina.
[0165] The specific surface area of shaped alumina is 201m 2 / g, and the pore volume is 0.98ml / g.
[0166] (2) Preparation of modified catalyst
[0167] In a round-bottom flask, 10g of formed alumina was mixed with 100g of 0.15mol / L sulfuric acid solution, heated to 70°C, and refluxed for 2 hours. The reaction system was cooled to room temperature and filtered to obtain a solid product. The solid product was washed 6 times with 100ml of deionized water, dried in air at 110°C for 8 hours, and then calcined at 400°C for 7h to obtain modified catalyst D4.
[0168] The specific surface area of modified catalyst D4 is 182m 2 / g, and the pore volume is 0.89ml / g.
[0169] (3) Catalyst reaction performance evaluation
[0170] The esterification performance of catalyst D4 was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 82.9%, and the selectivity of methyl methacrylate was 94.3%.
[0171] Comparative Example 5
[0172] The composite catalyst was prepared in the same manner as in Example 1, except that:
[0173] Eliminate step (1) in Example 1;
[0174] The “microporous-mesoporous composite material A” in step (2) of Example 1 was replaced with “commercially available silicon dioxide (purchased from Qingdao Hailang Silica Gel Desiccant Factory, with a specific surface area of 329 m 2 / g, pore volume 0.6cm 3 / g)”.
[0175] The catalyst D5 was obtained, and the specific surface area of D5 was 382m 2 / g, and the pore volume is 0.4ml / g.
[0176] The catalytic performance of catalyst D5 was tested using the same esterification reaction performance evaluation method as in step (3) of Example 1; the results showed that the methacrylic acid conversion was 79.8% and the selectivity for methyl methacrylate was 93.7%.
[0177] Comparative Example 6
[0178] The microporous-mesoporous composite material A was prepared in the same manner as step (1) of Example 1.
[0179] Cancel step (2).
[0180] The microporous-mesoporous composite material A was used as catalyst D6, and the catalytic performance of catalyst D6 was tested according to the same esterification reaction performance evaluation method as step (3) in Example 1. The results showed that the methacrylic acid conversion rate was 32.7%, and the selectivity of methyl methacrylate was 90.8%.
[0181] It can be seen from the above results that the modified composite catalyst provided by the present invention can directly convert methacrylic acid and methanol into methyl methacrylate, thereby obtaining a higher methacrylic acid conversion rate and methyl methacrylate selectivity.
[0182] In Comparative Example 1, in the microporous-mesoporous composite material, the content of ZSM-35 molecular sieve is too high and the content of alumina is low. Since the distribution of micropores and mesopores on the microporous-mesoporous composite material is not within the scope defined by the present invention, it will affect the molecular diffusion during the reaction. In addition, the conditions and parameters in the preparation process of the modified composite catalyst are not within the scope defined by the present invention, resulting in poor modification effect. The above two reasons ultimately lead to a low conversion rate of methacrylic acid and a low selectivity of methyl methacrylate.
[0183] In Comparative Example 2, in the microporous-mesoporous composite material, the content of ZSM-35 molecular sieve is low and the content of aluminum oxide is high. Since the content of ZSM-35 molecular sieve with certain acidity on the microporous-mesoporous composite material is too low, the active center sites in the reaction are insufficient. Moreover, the conditions and parameters in the preparation process of the modified composite catalyst are not within the scope defined by the present invention, so that the modification effect is poor. The above two reasons ultimately lead to a low conversion rate of methacrylic acid and a low selectivity of methyl methacrylate.
[0184] In Comparative Example 3, the molded zeolite molecular sieve material contains only ZSM-35 molecular sieve and no alumina. Since the material contains only microporous channels and no mesoporous channels, it will affect the molecular diffusion during the reaction, resulting in low methacrylic acid conversion and low selectivity for methyl methacrylate.
[0185] In Comparative Example 4, the molded alumina material contains only alumina but does not contain ZSM-35 molecular sieve with certain acidity, resulting in insufficient active center sites in the reaction, resulting in low methacrylic acid conversion rate and low selectivity for methyl methacrylate.
[0186] In Comparative Example 5, the modified composite catalyst does not contain the microporous-mesoporous composite material, and is replaced by silica gel. Since silica gel does not have the pore characteristics of the microporous-mesoporous composite material, the conversion rate of methacrylic acid is low and the selectivity of methyl methacrylate is low.
[0187] In Comparative Example 6, since the alumina was only composited with the ZSM-35 molecular sieve without sulfuric acid acidification treatment, the surface acidity of the obtained microporous-mesoporous composite material was still weak, resulting in low methacrylic acid conversion rate and low selectivity for methyl methacrylate.
[0188] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified composite catalyst, characterized in that: The pore size of the modified composite catalyst is bimodal, with a first pore size of 0.4-0.6 nm and a second pore size of 9-15 nm; the modified composite catalyst is obtained by acidification treatment of a microporous-mesoporous composite material, wherein the microporous-mesoporous composite material includes a hydrogen-type ZSM-35 molecular sieve and alumina, and based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 30-90% by weight, and the content of the alumina is 10-70% by weight.
2. The modified composite catalyst according to claim 1, wherein The pore size of the modified composite catalyst is bimodal, with a first pore size of 0.5-0.6 nm and a second pore size of 9.8-14.8 nm.
3. The modified composite catalyst according to claim 1 or 2, wherein The specific surface area of the modified composite catalyst is 220-380m 2 / g, pore volume is 0.2-0.8cm 3 / g; Preferably, the specific surface area of the modified composite catalyst is 250-350m 2 / g, pore volume is 0.3-0.7cm 3 / g; More preferably, the specific surface area of the modified composite catalyst is 287-331m 2 / g, pore volume is 0.4-0.6cm 3 / g.
4. The modified composite catalyst according to claim 1, wherein Based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 40-80% by weight, and the content of the alumina is 20-60% by weight; More preferably, based on the total weight of the microporous-mesoporous composite material, the content of the hydrogen-type ZSM-35 molecular sieve is 50-70% by weight, and the content of the alumina is 30-50% by weight.
5. The modified composite catalyst according to claim 1 or 4, wherein The specific surface area of the microporous-mesoporous composite material is 250-400 m 2 / g, pore volume is 0.3-0.9cm 3 / g; Preferably, the specific surface area of the microporous-mesoporous composite material is 280-370 m 2 / g, pore volume is 0.4-0.8cm 3 / g; More preferably, the specific surface area of the microporous-mesoporous composite material is 304-344m 2 / g, pore volume is 0.5-0.7cm 3 / g.
6. The modified composite catalyst according to any one of claims 1 to 5, wherein The preparation method of the microporous-mesoporous composite material comprises: The hydrogen-type ZSM-35 molecular sieve, the aluminum-containing precursor and the extrusion aid are mixed and then contacted with dilute nitric acid, and a microporous-mesoporous composite material is obtained after stirring, extrusion molding, drying and calcination.
7. The modified composite catalyst according to claim 6, wherein The aluminum-containing precursor is selected from one or more of pseudo-boehmite, aluminum sol, boehmite and aluminum hydroxide gel, preferably pseudo-boehmite.
8. The modified composite catalyst according to claim 6, wherein The concentration of the dilute nitric acid is 0.5-15%, preferably 1-10%; And / or, the weight ratio of the hydrogenated ZSM-35 molecular sieve, the aluminum-containing precursor and the extrusion aid is 1:(0.1-3.5):(0.03-0.40), preferably 1:(0.3-2.5):(0.05-0.30); And / or, the calcination conditions include: a temperature of 450-650° C. and a time of 3-20 hours.
9. A method for preparing a modified composite catalyst according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) contacting the microporous-mesoporous composite material with an aqueous acid solution to react and obtain a mixture; (2) The mixture is filtered, washed, dried and calcined to obtain a modified composite catalyst.
10. The preparation method according to claim 9, wherein: The acid is sulfuric acid; and / or, the molar concentration of the aqueous solution of the acid is 0.05-0.3 mol / L, preferably 0.1-0.2 mol / L; and / or, the weight ratio of the microporous-mesoporous composite material to the acid aqueous solution is 1:(3-50), preferably 1:(5-30); And / or, the calcination conditions include: temperature of 300-500° C. and time of 3-15 h.
11. Use of the modified composite catalyst according to any one of claims 1 to 8 in the synthesis reaction of methyl methacrylate.
Citation Information
Patent Citations
Catalyst for preparing acrylic acid and methyl acrylate
CN108097286A
Method of synthesizing dimerized methyl glycolate with meso / micro-porous composite molecular sieve catalyst
CN108689844A
Methacrylic acid esterification catalyst as well as preparation method and application thereof
CN115487858A
Forming esterification catalyst, preparation method thereof and application of forming esterification catalyst in synthesis of isoamyl acetate
CN115487861A
Catalyst for synthesizing methyl methacrylate as well as preparation method and application of catalyst
CN115608406A